A Critical analysis of the Views of Ibn Warraq about the Historical status of Mushaf ibn e Mas’ud - Nasreen, Hafsa (Journal of Islamic and Religious Studies, 2017)
This article deals with the polemics of Ibn Warraq about the history of the text of Qur’an with reference the codex of Abdullah bin Mas’ud. Ibn Warraq considers the codex of Ibn Mas’ud as milestone in the history of Qur’anic text. Ibn Warraq is of the view that its order of Sura is different from Mushaf Uthmani and a lot of variant reading have been attributed to him so the history of Qur’anic text and the text itself should be rearranged in the light of codex of Ibn Masud. In this paper these views being examined in the light of authentic sources.